Lack of correlation of 24-vs. 48-h itraconazole minimum inhibitory concentrations with microbiological and survival outcomes in a guinea pig model of disseminated candidiasis - ODABAŞI, ZEKAVER (WILEY, 2010)
P>A 'trailing' effect has been commonly observed when azole antifungals are tested against Candida spp. Previous experience with fluconazole indicates that 24-h minimum inhibitory concentration (MIC) values are more compatible endpoints when compared with clinical outcomes. We evaluated the trailing effect of Candida isolates tested with itraconazole in a guinea pig model of systemic candidiasis. Survival and organ burden were only significantly affected by using a higher dose of itraconazole, irrespective of the MIC differences at 24 and 48 h. A fluconazole-resistant strain with susceptible dose-dependent MICs to itraconazole was successfully treated with high-dose itraconazole. Our data suggests that survival and microbiological response depend more on drug dosing than on the trailing phenotype of the isolates.
Keywords: Itraconazole; trailing effect; candidiasis; ANTIFUNGAL SUSCEPTIBILITY TEST; IN-VITRO; BROTH MACRODILUTION; MULTICENTER EVALUATION; MURINE MODEL; MICRODILUTION; FLUCONAZOLE; 5-FLUOROCYTOSINE; QUANTITATION; INFECTION